IMPLEMENTASI KURIKULUM MUATAN LOKAL BERBASIS PESANTREN DI SMP A. WAHID HASYIM TEBUIRENG JOMBANG - Nurkayati, Siti (Jurnal Studi Islam dan Sosial, 2020)
This research aims to examine the implementation of the local Islamic boarding school-based curriculum at SMP A. Wahid Hasyim Tebuireng Jombang. This research uses a qualitative-descriptive approach, with data collection techniques: observation, interviews and documentation. The results of this research show: 1) There is more Islamic boarding school-based local content curriculum at SMP A. Wahid Hasyim Tebuireng than in SMP schools in general. Islamic boarding school lessons are usually only available in madrasa schools, but at A. Wahid Hasyim Middle School, almost 40 percent of general lessons. 2) There are three supporting and inhibiting factors in implementing Islamic boarding school-based local content learning, namely the existence of a program to improve the quality of human resources (teacher training); adequate facilities and infrastructure; Islamic boarding school-based local content teachers have adequate competence and expertise in their field. Meanwhile, the inhibiting factors are students' lack of interest in learning; input of students from public elementary schools; limited time allocation for Arabic language subjects